2008
DOI: 10.1007/s00192-008-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of the female pelvic floor: towards treatment a la carte of the “geripause”

Abstract: When you are old and grey and full of sleep, And nodding by the fire, take down this book, And slowly read, and dream of the soft look, Your eyes had once, and of their shadows deep. William Butler Yeats The study of menopause and female ageing "geripause" is receiving much attention lately from the health care community for three main reasons [1-3]. The first is the global increase in female life expectancy as a result of improved health awareness and services with continuing reduction of adult mortality, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Oestrogen deficiency at menopause is widely considered as a contributing factor for pelvic floor dysfunction due to presence of oestrogen receptors in supportive pelvic floor disorders although long-term benefits after oestrogen replacement has not been analysed in most studies. 6 …”
Section: Etiology Of Pelvic Floor Disordermentioning
confidence: 99%
“…Oestrogen deficiency at menopause is widely considered as a contributing factor for pelvic floor dysfunction due to presence of oestrogen receptors in supportive pelvic floor disorders although long-term benefits after oestrogen replacement has not been analysed in most studies. 6 …”
Section: Etiology Of Pelvic Floor Disordermentioning
confidence: 99%
“…Ghrelin is a recently discovered 28 amino acid peptide hormone that was initially identified as an endogenous ligand for growth hormone (GH) stimulating hormone receptor in rat and human stomach and is the only known orexigenic gut hormone [8,9]. Levels of circulating ghrelin have been noted to increase before meals and fall rapidly after eating [8].…”
mentioning
confidence: 99%
“…A decrease in circulating ghrelin has also been found following bypass operations and may be responsible for the long-term weight loss following bariatric surgery. Ghrelin receptors are expressed in the pituitary gland and hypothalamus as well as a wide variety of peripheral tissues including the urethra, urinary bladder, and anal canal of rats [8][9][10]. Recent animal studies have shown that ghrelin also has important anti-aging function on the pelvic floor [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations